A novel surgical technique for cervical laminoplasty in patients with multilevel cervical spondylotic myelopathy: A case report and literature review - Huang, Xinyi; Liu, Daming; Yang, Yipeng; Qiu, Haiyang; Ma, Zhensheng; Lei, Wei; Zhang, Yang (Frontiers in Surgery, 2023)
Cervical laminoplasty is a posterior-based surgical decompression technique for the treatment of multilevel cervical spondylotic myelopathy (CSM) that may improve the preservation of cervical mobility, spinal canal structure, and natural lordosis. Although this procedure is considered to be comparatively safe, with fewer complications than those seen with laminectomy, several postoperative problems have been noted, including axial neck pain, C5 nerve palsy, and failed resolution of radiculopathy. Hence, various modifications have been made to improve the safety and effectiveness of this technique. Here, we report the case of a 74-year-old man with multilevel CSM who underwent posterior cervical laminoplasty in the C3–C7 segments using a novel surgical technique, termed alternating-side cervical laminoplasty. Preoperative and postoperative assessments, including visual analog scale (VAS), modified Japanese Orthopaedic Association (mJOA), neck disability index (NDI) scores, and imaging data, were collected and analyzed. The results of a five-year follow-up indicated that the patient recovered well, with no development of axial neck pain. This is the first report of this modified open-door laminoplasty, which we propose may be a better surgical option for preventing postoperative axial neck pain in patients with multilevel CSM. Additionally, opening the laminae on the alternating sides during laminoplasty could provide a flexible approach to complete decompression on different radiculopathy sides.